Technological change and the effectiveness of domestic government agencies and international organisations. How does technological change impact the effectiveness and benign political character of domestic government agencies and international organisations? - van Zyl, Jacqualine Frances (Department of Political Studies, 2021)
Studies examining the relationship between technological advancements and politics demonstrate that this relationship remains closely connected. Numerous research efforts have focused on unpacking and further understanding this relationship to develop a better idea on the ways in which technology has acted as a motor of history, driving the transformation of factors such as class structures, ideas and institutions across the globe. This research is guided by an understanding and acknowledgement of the political nature of technological development. In highlighting this link, a valuable foundation for understanding this relationship is achieved, which is necessary when seeking to explore the ways in which innovative technologies influence the effectiveness and benign political character of domestic government agencies and international organisations. In order to ensure that an evaluation of the ways in which innovative technologies can impact the effectiveness and benign political character of domestic government agencies and international organisations is undertaken, this research is focused on firstly unpacking the relationship between technological advancement and politics through the use of a comprehensive literature review. It remains imperative to note that the study on the relationship between technological advancement and politics is incredibly broad. As such, for the purposes of this research emphasis will be placed on dealing with a small and focused aspect of this relationship, namely the impact of technological advancements on the effectiveness and benign political character of domestic government agencies and international organisations. Through examining the work of scholars that have undertaken research focused on technological advancements and the impacts this has on politics and vice versa, a holistic understanding on the topic is achieved. Key arguments presented by scholars such as Feenberg, Ganne, Kamel and Sussman will be studied to ensure a rich vein of knowledge on the complex relationship of technology and politics is developed. Once this understanding has been established, an examination into two key schools of thought, namely technology as a tool of control or domination, and technology as a benign instrumental force are studied to highlight the main arguments presented by scholars that have studied the topic over decades. In order to ensure that an in-depth analysis is achieved, the positive and negative impacts of technological advancements on politics will be explored through assessing arguments presented by scholars that are focused on understanding the ways in which politics and technology are related. An examination into the ways in which innovative technologies can be leveraged to enhance the operations and benign political character of domestic government agencies and international organisations will be undertaken. For the purposes of this research, blockchain technology has been selected as the innovative technology to be studied in relation to how domestic government agencies and international organisations can harness the opportunities presented by the technology. As such, an in-depth explanation into blockchain technology will be presented as well as a discussion pertaining to the opportunities and challenges associated with this technology. When examining the opportunities presented by blockchain technology two key features, namely improved transparency as well as efficient and cost-effective international payments will be discussed. With regards to the challenges associated with the use of blockchain technology, issues such as infrastructural infancy, limited organisational capacities, data privacy concerns and issues of governance will be outlined and discussed. This will ensure that an in-depth understanding into blockchain technology and its uses is demonstrated, which in turn contributes to a sound understanding when analysing the selected case studies used in this research. Once an understanding of the relationship between technological advancements and politics, as well as blockchain technology and its uses is established an analysis of the four selected case studies can be undertaken and effectively comprehended. For the purposes of this research, a case study methodology has been selected in terms of the focus on the use of blockchain technology. This is an area of study in which there has been much academic research conducted, but there are few analytically powerful theories that can help us understand recent technological changes. The potential impact of contemporary technological innovations, such as Blockchain, remains poorly understood. This study will use exploratory case studies to identify key processes and questions for further study, including concerning how the notions of “effectiveness” and “benign character” might be clarified and operationalised in further studies. A multi-case study approach has been taken in relation to the selection of examples included as case studies. These cases have been chosen both from the operations of domestic agencies and from the operations of international organisations in order to shed preliminary light on the differences between the domestic and international spheres of political and administrative activity. In order to begin to assess the ways in which innovative technologies influence the operations and benign political character of domestic government agencies and international organisations, four key case studies have been selected to be included in this research. An assessment into the “e-Estonia” case study, where essential services and information flows were significantly improved as a result of the digitalisation of services made possible due to effective collaborations between by public and private sectors will be discussed as the first key case study. Secondly, an examination into the South African Reserve Bank's “Project Khokha” will demonstrate the opportunities and benefits associated with intentional research and exploration into the use of innovative technologies to enhance operations of domestic government departments. The e-Estonia and “Project Khokha” case studies are included in this research as they demonstrate the ways in which domestic government agencies have explored the use of technology to enhance their operations, while also highlighting key lessons learnt in the implementation of these projects. An assessment of the World Food Programme's “Building Blocks” initiative, will demonstrate the value of the exploration of innovative technologies such as blockchain for international organisations. This initiative demonstrates the ability of blockchain-based solutions to enhance operations and the distribution of aid for international organisations such as the World Food Programme. Finally, the UNICEF's Venture Fund has been included as a case study in this research to explore and demonstrate the ways in which disruptive technologies can be harnessed for positive change on a global scale. Through the use of the case studies listed above, the research will explore how and whether opportunities and potential are presented by innovative technologies such as blockchain for both domestic government agencies and international organisations. This research will also seek to understand barriers that currently exist when looking to implement blockchain-based solutions across the globe, how these limitations can be understood, and whether they are likely to be overcome with increased knowledge of the technology, and greater contributions by scholars interested in understanding the ways in which domestic government agencies and international organisations can enhance their operations through embracing innovative technologies.